6(k-74)-5=83

Simple and best practice solution for 6(k-74)-5=83 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(k-74)-5=83 equation:


Simplifying
6(k + -74) + -5 = 83

Reorder the terms:
6(-74 + k) + -5 = 83
(-74 * 6 + k * 6) + -5 = 83
(-444 + 6k) + -5 = 83

Reorder the terms:
-444 + -5 + 6k = 83

Combine like terms: -444 + -5 = -449
-449 + 6k = 83

Solving
-449 + 6k = 83

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '449' to each side of the equation.
-449 + 449 + 6k = 83 + 449

Combine like terms: -449 + 449 = 0
0 + 6k = 83 + 449
6k = 83 + 449

Combine like terms: 83 + 449 = 532
6k = 532

Divide each side by '6'.
k = 88.66666667

Simplifying
k = 88.66666667

See similar equations:

| 6=4-w | | x+17=5x+5 | | 6=-3(d-9) | | 2(7x+8)-4=28 | | 288=X+0.06X | | t-7/3=3 | | 4x+31=x+7 | | 12/n=3 | | 4x+11=x+1 | | 2/3x5/6x | | 8-51nx=3 | | 5x-26=x+6 | | x+(x*0.3)=5540.12 | | (x+(x*0.3))=5540.12 | | (X*.4)+X=4250 | | (2*.4)+X=4250 | | X*5+9=34 | | 9X*.40+X=4250 | | 6y=4y+24 | | 2X*.5=4250 | | x^3+x^2+x-20=0 | | 5x-12=-2+5 | | Y+1(33)-28=21 | | 10n+50=5n-25 | | 3y^2+2x-1=0 | | 3x-5x-120=0 | | -6n+3=-9 | | 2x-44=4x-88 | | 4n+10=2n-5 | | N-6=21-8n | | 9x+10y=500 | | (n-6)+6=12 |

Equations solver categories